1998
DOI: 10.4269/ajtmh.1998.59.883
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate versus artemether for the treatment of recrudescent multidrug-resistant falciparum malaria.

Abstract: Abstract. The therapeutic efficacy and toxicity of artesunate (2mg/kg/day for five days, then 1 mg/kg/day for two days: total ϭ 12 mg/kg) was compared with that of artemether (4 mg/kg followed by 2 mg/kg/day for two days, then 1 mg/kg/day for four days: total ϭ 12 mg/kg) for the treatment of recrudescent multidrug-resistant falciparum malaria in an open randomized trial in 443 patients living on the western border of Thailand. Parasite and fever clearance times were similar in both groups; within 48 hr 94% (95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 17 publications
2
51
1
Order By: Relevance
“…Studies involving 2,593 of the patients described here have been reported previously. [6][7][8][9][10][11][12][13] The epidemiology of malaria at this site has also been described in detail recently. 14 Transmission of malaria is low (approximately one vivax, and one falciparum malaria infection per person every two years) and seasonal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies involving 2,593 of the patients described here have been reported previously. [6][7][8][9][10][11][12][13] The epidemiology of malaria at this site has also been described in detail recently. 14 Transmission of malaria is low (approximately one vivax, and one falciparum malaria infection per person every two years) and seasonal.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment with one of the drug regimens (Table 1) was assigned to patients in comparative randomized studies as described previously. [6][7][8][10][11][12][13] Drug administration was observed in all cases. If vomiting occurred Ͻ 30 min after drug administration, the full dose was repeated, and if vomiting occurred between 30 and 60 min, half the dose was repeated.…”
Section: Methodsmentioning
confidence: 99%
“…This was intended speci¢cally to delay the onset of resistance to me£oquine (Peters & Robinson 1984), but it did not work because P. falciparum in Thailand was already highly resistant to pyrimethamine^sulphadoxine. More recently, artemisinin and its derivatives have been combined with other antimalarials, notably me£oquine, and have accelerated recoveries, increased cure rates, reduced transmissibility, and appear also to have delayed the development of further resistance and reduced the incidence of disease (Price et al 1997). The rationale behind antimalarial combinations, and suggestions for future use of this strategy to treat all malaria are presented below.…”
Section: (N) Drug Combinationsmentioning
confidence: 99%
“…[1][2][3][4] As part of the strategy to combat the spread of antimalarial drug resistance globally, the World Health Organization recommended the use of artemisininbased combination therapies (ACTs) because they quickly reduce the burden of parasitemia and gametocytemia and the chance of drug resistance. 1,[5][6][7][8][9] Artesunate-mefloquine (AMQ) combination is not considered a viable option for use as first-line therapy in Africa because of intense transmission. 2 However AMQ, co-packaged as well as fixed dose formulations, is readily available and used in Africa.…”
Section: Introductionmentioning
confidence: 99%